Hypothermia in preterm infants admitted to low-resource neonatal units in northern Nigeria: an observational study of occurrence and risk factors - Usman Abiola Sanni; Fatima Usman; Taofik Oluwaseun Ogunkunle; Adamu Sa'idu Adamu; Audu Isah Lamidi; Taslim Olatunde Lawal; Surajudeen Oyeleke Bello; Aliyu Mamman Na'uzo; Tajudeen Lanre Ibrahim; Nyirimanzi Naphtal; Sa'adatu Shehu; Abdullahi Jibrin; et al. (BMC, 2024)
Abstract Background Hypothermia is an important cause of morbidity and mortality among preterm and low-birth-weight neonates. In resource-constrained settings, limited referral infrastructure and technologies for temperature control potentiate preterm hypothermia. While there is some documentation on point-of-admission hypothermia from single center studies, there are limited multicenter studies on the occurrence of hypothermia among preterm infants in resource-limited-settings. Therefore, we conducted a multicenter study to determine the prevalence and risk factors for hypothermia at the time of admission and during the first 72 h after admission in northern Nigeria. Method We carried out a prospective cohort study on preterm infants admitted to four referral hospitals in northern Nigerian between August 2020 and July 2021. We documented temperature measurements at admission and the lowest and highest temperatures in the first 72 h after admission. We also collected individual baby-level data on sociodemographic and perinatal history data. We used the World Health Organization classification of hypothermia to classify the babies' temperatures into mild, moderate, and severe hypothermia. Poisson regression analysis was used to identify risk factors for moderate-severe hypothermia. Results Of the 933 preterm infants enrolled, 682 (72.9%) had hypothermia at admission although the prevalence of hypothermia varied across the four hospitals. During the first 24 h after admission, 7 out of every 10 babies developed hypothermia. By 72 h after admission, between 10 and 40% of preterm infants across the 4 hospitals had at least one episode of moderate hypothermia. Gestational age (OR = 0.86; CI = 0.82-0.91), birth weight (OR = 8.11; CI = 2.87-22.91), presence of a skilled birth attendant at delivery (OR = 0.53; CI = 0.29-0.95), place of delivery (OR = 1.94 CI = 1.13-3.33) and resuscitation at birth (OR = 1.79; CI = 1.27-2.53) were significant risk factors associated with hypothermia. Conclusion The prevalence of admission hypothermia in preterm infants is high and hypothermia is associated with low-birth-weight, place of delivery and presence of skilled birth attendant. The prevalence of hypothermia while in care is also high and this has important implications for patient safety and quality of patient care. Referral services for preterm infants need to be developed while hospitals need to be better equipped to maintain the temperatures of admitted small and sick newborns.